Market Maker Movements in Sharia Stocks from the Perspective of Maqaṣid Syariah and Fiqh Muamalah - Akmal Falasifa; Muhyidin Muhyidin; Nashihin Nashihin (Al Wajiz: Journal of Sharia and Economics Studies, 2025)
This study aims to analyze the practice of bandar movement (market maker activity) in Islamic stocks from the perspective of fiqh mu‘āmalah and maqāṣid al-sharī‘ah. The phenomenon of market maker activity is important to examine because it can affect price stability, market fairness, and investor trust in the Islamic economic system. This research employs a qualitative approach based on library research, examining primary sources such as the Qur’an, hadith, classical fiqh books, and DSN-MUI Fatwa No. 80/DSN-MUI/III/2011, as well as secondary literature related to the Islamic capital market and stock price manipulation. The results show that not all bandar activities are negative; practices such as market making and price stabilization can be justified as they help maintain market liquidity and efficiency. However, other forms such as pump and dump, wash trading, spoofing, cornering, and front running are considered contrary to the principles of honesty (ṣidq), trustworthiness (amānah), and justice (al-‘adl) in fiqh mu‘āmalah, and they violate the objectives of maqāṣid al-sharī‘ah in preserving wealth (ḥifẓ al-māl) and intellect (ḥifẓ al-‘aql). This study emphasizes the need for more ethical and maqāṣid-based supervision of the Islamic capital market to safeguard public welfare in modern investment practices.